MY BOARDING HOUSE START-UP PLAN - Karvalo Imam Jonathan; Rachel Setiawan; SUCIANI AMBARWATI; M. Usman Saputra; Nurfitri Raudhatul Jannah; Tiara Fitari (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
Start-up Kosanku is present in Bangka Belitung Province as an innovative solution to make finding temporary housing easier, especially for students, professional workers and tourists. Through digital applications, Kosanku offers boarding house rental services with easy access, competitive prices and complete facilities that suit the needs of various customer segments. Kosanku's marketing strategy focuses on clear market segmentation, targeting students and professional workers, as well as positioning that prioritizes user convenience and comfort. In addition, financial analysis is carried out to map variable costs, fixed costs and sales projections to optimize business profitability. With the support of digital-based marketing strategies and partnerships with local boarding house owners, Kosanku aims to create an effective and efficient rental experience, and support the growth of the digital economy in Bangka Belitung. The analysis results show that Kosanku has great potential to develop in the local market, especially in facing the increasing need for temporary housing in the province.